An estimation of the hidden economy in Greece (1960-2000) - Κασσάρ, Γεώργιος; Παλαιολόγος, Γιάννης (SPOUDAI Journal of Economics and Business, 2003)
While Hidden Economy (and the Tax Evasion) is a potentially important phenomenon in the Greek Economy, its implications in our economy only during the last fifteen years, have started to be examined by the researchers through the construction of econometric models. Moreover, the issue of Hidden Economy internationally have started to be investigated from the Economic Institutions mainly from the beginning of 1980's. The work of Gutmann in 1977 gave the motivation to the other economists to show an interest for the Hidden Economy. The implementation of nominal convergence criteria of the Greek Economy towards the zone of Euro, according to Maastricht Treaty, became the cause to be understood the importance of Hidden Economy phenomenon by the economic policy makers. The reduction of Hidden Economy will contribute to the drastic diminution of Public Deficits as well as the Public Debt of the Greek Economy. Today, according to the data of International Monetary Fund (IMF), Greece is the country with the higher Hidden Economy in E.U. Particularly, the 1/3 of the Greek Economy, in other words the 28,7% of GDP, is Hidden Economy and therefore is untaxed. JEL Classification: C10